Heavy metal ion discrimination based on distinct interaction between single-stranded DNA and methylene blue. Issue 1 (23rd November 2018) - Li, Li; Liu, Bing; Chen, Zhengbo
Abstract : In this work, we developed a facile and extensible colorimetric sensor array based on different interactions between methylene blue (MB) and single-stranded DNA (ssDNA) for the discrimination of heavy metal ions. Abstract : In this work, we developed a facile and extensible colorimetric sensor array based on different interactions between methylene blue (MB) and single-stranded DNA (ssDNA) for the discrimination of heavy metal ions. Different target metal ions can make MB exhibit diversified color and absorbance changes in the presence of different types of DNA as receptors. Linear discriminant analysis (LDA) results give clear identification of each heavy metal ion on a two-dimensional (2D) spatial dispersion plot. Therefore, a new sensor array composed of three types of ssDNA as receptors and MB as a colorimetric probe is designed for fast discrimination of metal ions, and it achieves accurate discrimination of 9 species of heavy metal ions at 30 nM in buffer and tap water samples.